Painlevé Integrability and mixed P_III-P_V system solutions - Alves, Victor César Costa [UNESP] (2017)
The current work aims at applications of mathematical methods of Painlevé integrability in physics, on the other side it also approaches the integrable hierarchies formalism and the 2M-bose model where differential equations methods are used as well as a method for solutions using Padé approximants.